2015
DOI: 10.2516/ogst/2015022
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Experimental and Numerical Investigation of the Flow through the Intake Port of an Internal Combustion Engine

Abstract: -Modern spark-ignited internal combustion engines have intake ports designed to introduce high levels of so-called "tumble" charge motion. Correspondingly high shear rates can lead to high fluctuations and turbulence within the combustion chamber. A suitable test case to characterize the intake flow is a steady-state flow bench. Although routinely used in the engine development process to determine the global discharge coefficients, only a few detailed numerical and experimental studies use this test case to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
(23 reference statements)
1
23
0
1
Order By: Relevance
“…With increasing z + values, the dimensionless velocity profiles exhibit larger deviations and no agreement with the log-formulation of the CBLA is found. This is consistent with observations in [10][11][12]52], confirming that no turbulent equilibrium boundary layer exists at the piston surface. However, it is interesting to note that the results for P1 and P3 are closer to the CBLA, while the profiles for P2 and P4 show the largest discrepancies.…”
Section: Piston Boundary Layersupporting
confidence: 81%
See 2 more Smart Citations
“…With increasing z + values, the dimensionless velocity profiles exhibit larger deviations and no agreement with the log-formulation of the CBLA is found. This is consistent with observations in [10][11][12]52], confirming that no turbulent equilibrium boundary layer exists at the piston surface. However, it is interesting to note that the results for P1 and P3 are closer to the CBLA, while the profiles for P2 and P4 show the largest discrepancies.…”
Section: Piston Boundary Layersupporting
confidence: 81%
“…To minimize numerical diffusion, a central differencing scheme is used in space and a second-order backward scheme in time. The solver's suitability for SRS in IC engines has been shown in previous works [6,8,11,21,28].…”
Section: Numerical Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that Scale-Resolving Simulations (SRS) can capture the flow field correctly [16][17][18][19][20], considering a reduced number of phenomena in simple geometries. In contrast, a previous study on the flow bench identified discrepancies between Computational Fluid Dynamics (CFD) and Particle Image Velocimetry (PIV) [21], attributable to the complexity of the flow field. This motivated further studies.…”
Section: Introductionmentioning
confidence: 61%
“…The experimental arrangement is similar to that in a previous work [21], but for completeness a brief overview is given here. Figure 4 shows the Computer Aided Design (CAD) model of the intake system, the cylinder head, and the outlet tube of the flow bench.…”
Section: Experimental Studiesmentioning
confidence: 98%